JOB SATISFACTION AMONG THE ACADEMIC STAFF OF A SAUDI UNIVERSITY: AN EVALUATIVE STUDY - Al-Rubaish, Abdullah M. (Medknow Publications & Media Pvt Ltd, 2009)
BACKGROUND: Job satisfaction is a major determinant of job performance, manpower retention and employee well-being. OBJECTIVES: To explore the state of job satisfaction among the academic staff of King Faisal University – Dammam (KFU-D), and detect the areas and groups at a higher risk of being dissatisfied. METHOD: A fully-structured 5-option Likert-type Job Satisfaction Questionnaire (JSQ) composed of an evaluative item and eleven domains making a total of 46 items was used. It was distributed by internal mail to all the 340 academic staff, 248 of whom returned completed questionnaires (response rate = 72.9 %). FINDINGS: The overall mean Job Satisfaction Rate (JSR) was 73.6 %. The highest JSR's were found in three domains (“Supervision”, “Responsibility”, and “Interpersonal Relationships”), and the lowest in four others (“Salary”, “My Work Itself”, “Working Conditions”, and “Advancement”). The JSR was significantly lower among Saudi nationals, females, those below age 40, those from clinical medical and Dentistry departments. Multiple Regression identified six independent variables which conjointly explained 25 % of the variance in job satisfaction (p < 0.0001). These were: being an expatriate, above the age of 50, serving the university for less than one or more than ten years, and, not from a clinical department of Medicine or Dentistry. CONCLUSIONS: Most staff were satisfied with many aspects of their jobs, but there was significant dissatisfaction with several job-related aspects and demographic features. Appropriate interventions are indicated. Further studies are needed to confirm the present findings and to monitor future trends.